ARCHAEOLOGICAL EXPLORATION ON ORLINA HILL (MOUNT KHOJA–GULSUAR) - Aripdjanov O.Y.; Gorin A.N. (Western European Studies, 2024)
On November 5, 2011, the authors of the data were collected by the staff of the State Museum of History of Uzbekistan AN RUz by the intelligence work for the study of archeological monuments of the Termez district of the Surkhandarin region of the Republic of Uzbekistan. Osnovnoy tselyu dannogo issledovaniya yavlyalos izuchenie archeologicheskikh pamyatnikov antichnogo vremeni, raspolojennyx vdol pravogo berega reki Amudari.
Keywords: pravogo; berega; raspolojennyx; izuchenie